A New Method for the Bisymmetric Minimum Norm Solution of the Consistent Matrix Equations A1XB1=C1, A2XB2=C2 - Aijing Liu; Guoliang Chen; Xiangyun Zhang (Journal of Applied Mathematics)
We propose a new iterative method to find the bisymmetric minimum norm solution of a pair of consistent matrix equations A1XB1=C1, A2XB2=C2. The algorithm can obtain the bisymmetric solution with minimum Frobenius norm in finite iteration steps in the absence of round-off errors. Our algorithm is faster and more stable than Algorithm 2.1 by Cai et al. (2010).